The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1471-2407-14-447
|View full text |Cite
|
Sign up to set email alerts
|

CT based three dimensional dose-volume evaluations for high-dose rate intracavitary brachytherapy for cervical cancer

Abstract: BackgroundIn this study, high risk clinical target volumes (HR-CTVs) according to GEC-ESTRO guideline were contoured retrospectively based on CT images taken at the time of high-dose rate intracavitary brachytherapy (HDR-ICBT) and correlation between clinical outcome and dose of HR-CTV were analyzed.MethodsOur study population consists of 51 patients with cervical cancer (Stages IB-IVA) treated with 50 Gy external beam radiotherapy (EBRT) using central shield combined with 2–5 times of 6 Gy HDR-ICBT with or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 32 publications
6
70
2
Order By: Relevance
“…This difference was caused by the CS technique. According to other reports from Japan, although treatment outcomes were excellent, HR-CTV D90s were less than 70 Gy [18,19]. These results are also lower than our findings.…”
Section: Reported Treatment Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…This difference was caused by the CS technique. According to other reports from Japan, although treatment outcomes were excellent, HR-CTV D90s were less than 70 Gy [18,19]. These results are also lower than our findings.…”
Section: Reported Treatment Resultscontrasting
confidence: 57%
“…In addition, we continue to use a CS technique with EBRT and pelvic IMRT has not been accepted in the definitive RT for cervical cancer. Therefore, although successful outcomes were reported [18,19], RT for cervical cancer in Japan is still different from that in European countries in both BT and EBRT. In the immediate future, a new treatment protocol (MRI-or CT-based?…”
Section: Discussionmentioning
confidence: 99%
“…In ovarian cancer, RhoC overexpression promotes EMT, invasion, and metastasis, and RhoC knockout reverses the promoter role of vascular endothelial growth factor (VEGF) and transforming growth factor (TGF) in EMT [16]. In a previous study, we found that miR-93 downregulates RhoC to inhibit migration and invasion in ovarian cancer [17].…”
Section: Discussionmentioning
confidence: 99%
“…In ovarian cancer, Ras homolog family member C (RhoC) overexpression promotes EMT and increased migration and invasion ability [16]. In our previous study, we found that miR-93 downregulated RhoC to inhibit cell migration and invasion in ovarian cancer [17].…”
Section: Introductionmentioning
confidence: 99%
“…All brachytherapy was carried out by 192 Ir remote after loading system (RALS, Microselectron HDR ™ , Nucletron, Veennendaal, The Netherlands). From 2008, computed tomography (CT)-based image-guided ICBT for uterine cervical cancer patients was started in our department [16], and CT-based image-guided HDR-ISBT was started in the same year. Hybrid brachytherapy has started from 2010 for tumors with mild to moderate parametrial invasion that could not be adequately covered with ICBT [16, 17].…”
Section: Methodsmentioning
confidence: 99%